The Charter, General Ordinances, & c., of the City of Evansville 230 (1871) - (:unkn) unknown (My University, 1871)
§ 23: Prohibited keeping any gun or blasting powder in quantities greater than twenty-five pounds at one time. Also prohibited keeping such quantities in any other vessel than a tin canister, with a cover or stopper and the words "Gun Powder" labeled on it. Also prohibited selling gun powder after twilight.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER